A macro-level view of tourism sector between smartness and sustainability - Caputo, Francesco; Perano, Mirko; Mamuti, Agim (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
Adopting the interpretative lens provided by the studies on T-shaped, the paper proposes a conceptual framework to support a better understanding of managerial and organizational contributions in the field of tourism management. The domains of smartness and sustainability are analysed as key elements of macro-level dynamics in tourism sectors and the need for increasing the attention about the decision making dynamic in tourism management is underlined. The principal aim is to enrich previous managerial and organizational contributions in tourism sector identifying key paths and dimensions useful to improve the efficiency of tourism management in the next decades.